2022
DOI: 10.2147/cmar.s381316
|View full text |Cite
|
Sign up to set email alerts
|

A Dosimetric Study Comparing Different Radiotherapy Planning Techniques With and Without Deep Inspiratory Breath Hold for Breast Cancer

Abstract: To analyze whether deep inspiratory breath hold (DIBH) would be dosimetrically beneficial irrespective of radiotherapy planning techniques for patients with left breast cancers requiring adjuvant radiotherapy. Methods: Planning CT scans were taken in free-breathing (FB) as well as deep-inspiration breath hold (DIBH) for patients requiring adjuvant radiotherapy for left breast cancers. After registration, three radiotherapy plans -3D-conformal radiotherapy (3DCRT), intensity modulated RT (IMRT), and volumetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…This study offered information on potential utility of predictors for patients benefiting from DIBH. We studied some similar research ( 29 , 30 ). The investigation of comparing those parameters from FB and DIBH scans in some patients worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…This study offered information on potential utility of predictors for patients benefiting from DIBH. We studied some similar research ( 29 , 30 ). The investigation of comparing those parameters from FB and DIBH scans in some patients worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that the DIBH technique allows for heart preservation during the RT of the left breast, reducing the MHD by 26.2-75.0% compared to standard free-breathing (FB) and leaving the absolute MHD between 0.7-5.0 Gy [6,7]. The use of modern RT techniques with dose intensity modulation of the beam (IMRT) combined with DIBH can achieve even greater reductions in MHD [8]. Left lung dose reductions have also been observed with the DIBH technique [6,7].…”
Section: Introductionmentioning
confidence: 99%